GAYA KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN TEORI MICHIGAN DALAM MENINGKATKAN KINERJA GURU DI SMPIT UTSMAN BIN AFFAN SURABAYA - Wahyu Utami, Amira; Syifa Hadyan, Nazira; Helen Anggraeni, Fitriya; Aminah, Siti; Putri Naurha Ayu, Arinda; Putri Ahsyabila, Chantika; Dwi Anggraeny, Marsa; Roesminingsih, Erny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research intends to examine the leadership style of the principal as per Michigan Theory and its link to the performance of teachers at SMPIT Utsman bin Affan located in Surabaya. The central concern identified in this research is the presence of issues affecting teacher performance, including ineffective executive execution of teaching methods, insufficient innovation, and a need for enhanced work discipline, which are believed to be affected by the principal’s leadership approach. This study utilized a qualitative descriptive methodology, gathering data through interviews, observations, and analysis of documents. The results show that the principal employs a mixture of leadership styles, specifically focusing on both employee-centered and production-centered methods. The employee-centered style is demonstrated through open communication, a nurturing work atmosphere, and support for teachers, whereas the production-centered style is shown through defined task assignments, setting objectives, and frequent evaluations. The research also indicates a connection between the style of leadership and the performance of teacher, as well as the success of the educational process. Nonetheless, various challenges persist, including issues with time management, communication barriers, and differences in generations among the teaching staff.